Sistem Informasi Freelance Marketplace Berbasis WEB - Iqbal Fahrul Rahman (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
Nowadays, the state of the digital world is now experiencing a very rapid development of technological sophistication today, for example in the business world. The presence and development of digital services today makes every transaction activity, be it sales, marketing, and promotion of products and services, can be done online or digitally. In south Sumatra, especially in the city of Palembang, digital service business actors who are just starting a business are very unlikely to get consumers who choose the digital services they offer. And sometimes people find it difficult to find the digital services they need. With this, the researcher intends to design and build a website-based freelance marketplace information system to bring together service providers with service users in the digital world. The research method used is a prototype method which includes Communication, Planning Quickly, Modeling Design Quickly, Forming Prototypes, Handing Over Systems and Reciprocity. This website will be built using php programming language using codeigneter 3 framework and connected to MYSQL database.